Endocrine Disruptors Attitude Scale: A Scale Development Study - Miral, Mukaddes; Mamuk, Rojjin; Di?şsi?z, Melike; İşgüven, Šükriye Pınar (AVES, 2025)
Objective: Endocrine disruptors are substances and mixtures that cause health problems in individuals and generations by affecting the endocrine system. There is no measurement tool for the assessment of people’s attitudes toward endocrine disruptors. The development of a valid and reliable measurement tool for the measurement of the attitudes of adult individuals toward endocrine disruptors is the aim of this study. Methods: This study with a methodological design was conducted with 366 participants who were at least 18 years old and literate in Turkish between December 01, 2021, and March 01, 2022, in İstanbul and Famagusta. To collect data, the “Participant Introduction Form” and “Endocrine Disruptors Attitude Scale” were used. Data were evaluated with descriptive statistics, exploratory and confirmatory factor analysis, dependent samples t-test, Cronbach’s ? internal consistency coefficient, and Pearson correlation analysis. Results: When the item–total score correlations of 35 items in the draft scale were examined, 14 items with less than 0.30 and negative values were excluded from the scale. The correlation coefficient of all the remaining items was positive and significant (P < .001). The difference between test and retest mean scores was not statistically significant (P > .05). Cronbach’s ? reliability coefficient was determined as ? = 0.81 for the Consumer behavior sub-dimension, ? = 0.80 for Nutrition and hygiene, and ? = 0.85 for the whole scale. Conclusion: The scale is concluded to be a reliable and valid tool and can be utilized for determining the determination of attitudes of adults toward endocrine disruptors. © 2025 AVES. All rights reserved.
Keywords: Attitude; community health; endocrine disruptors; environment; questionnaire